2004
DOI: 10.1289/ehp.6647
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol uptake, toxicity, metabolism, and adverse effects on cadmium-treated amphibian embryos.

Abstract: The exposure of Bufo arenarum embryos to 25 µmol/L 17β-estradiol (E 2 ) resulted in 100% lethality within 48 hr, whereas 10 µmol//L E 2 was the no observed effect concentration value for shortterm chronic (7 days) exposure. The toxicity profile curves show that lethal effects were proportional to the E 2 concentration and the time of exposure. The E 2 uptake resulted in 20.1 ng E 2 /mg embryo at 8 hr posttreatment, but 67.3% of this value was achieved during the first 30 min of incubation with this estrogen. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…It is noteworthy that tadpoles exposed to 1.0 mg L -1 and above suffered 100 % mortality while no mortality occurred in the controls indicating high survival rates in uncontaminated water. Cd-induced mortality was also dose-dependent (Pearson correlation r = 0.92, p \ 0.001) which is consistent with results of Fridman et al (2004) observed in amphibians.…”
Section: Resultssupporting
confidence: 88%
“…It is noteworthy that tadpoles exposed to 1.0 mg L -1 and above suffered 100 % mortality while no mortality occurred in the controls indicating high survival rates in uncontaminated water. Cd-induced mortality was also dose-dependent (Pearson correlation r = 0.92, p \ 0.001) which is consistent with results of Fridman et al (2004) observed in amphibians.…”
Section: Resultssupporting
confidence: 88%
“…In rainbow trout, cadmium can act as an endocrine disrupter through alterations to oestrogen-regulated gene expression (LeGuevel et al, 2000;Vetillard and Bailhache, 2005). In amphibian embryos, exposure to oestradiol can be lethal and this effect could also be found following exposure to cadmium, and furthermore, exposure to cadmium and oestradiol simultaneously produced an additive effect on lethality (Fridman et al, 2004). These reports justify further research into the endocrine disrupting properties of cadmium and in vivo studies on other metalloestrogens are now needed.…”
Section: Evidence Of Oestrogenic Activity In Vivomentioning
confidence: 99%
“…Tripathi and Singh [12] reported the effects of cypermethrin and alphamethrin insecticides on the reproduction, hatching, and embryogenesis of an Indian freshwater pulmonate snail Lymnaea acuminata. Furthermore, L. luteola egg assay can also serve as a model species for an invertebrate embryo test, as, e.g., the subtropical zebra fish, Danio rerio for fish and vertebrates [13,14]. There are proteins [21].…”
Section: Introductionmentioning
confidence: 99%